2005
DOI: 10.7589/0090-3558-41.1.241
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Equine Encephalitis in a Free-ranging White-tailed Deer (Odocoileus virginianus)

Abstract: Eastern equine encephalitis (EEE) was diagnosed in a free-ranging, adult, male white-tailed deer (Odocoileus virginianus) from Houston County, Georgia, USA, in July 2001. The yearling buck had neurologic disease and died during transport to our diagnostic facility. Eastern equine encephalitis virus (EEEV) was isolated in Vero cell culture and identified by reverse-transcriptase polymerase chain reaction; as well, EEEV antigen was detected in brain by immunohistochemistry. This is the first report of fatal EEEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
4
30
1
Order By: Relevance
“…The overall seropositivity rate of 10.2% in this study is similar to the 14% rate found in Georgia and the 7.1% rate found in Maine in 2010. [17][18][19] Culiseta melanura, the primary enzootic vector, and Coquillettidia, Culex, and Aedes spp., which are likely bridge vectors of EEEV, have previously been documented in Vermont. 9,16 These potential bridge vectors are widely distributed in Vermont, but the distribution of Cs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall seropositivity rate of 10.2% in this study is similar to the 14% rate found in Georgia and the 7.1% rate found in Maine in 2010. [17][18][19] Culiseta melanura, the primary enzootic vector, and Coquillettidia, Culex, and Aedes spp., which are likely bridge vectors of EEEV, have previously been documented in Vermont. 9,16 These potential bridge vectors are widely distributed in Vermont, but the distribution of Cs.…”
Section: Discussionmentioning
confidence: 99%
“…The white-tailed deer has been shown to be a reasonable sentinel species that is frequently exposed to EEEV. [17][18][19][20] White-tailed deer also represent a large proportion of the mammalian source for blood meals for the most common bridge vector species. 21 In addition, white-tailed deer have a summer home range that is about 1 mile in radius, to which they return faithfully.…”
Section: Introductionmentioning
confidence: 99%
“…This species was selected as a sentinel for several reasons. First, several previous studies in the US (Hoff et al 1973, Bigler et al 1975, Tate et al 2005, Schmitt et al 2007) have reported EEEV antibody-positive sera among populations of free-ranging O. virginianus, demonstrating that deer frequently become infected with EEEV. Second, white-tailed deer form a significant proportion of the blood meals of EEEV bridge vectors, particularly Cq.…”
Section: Introductionmentioning
confidence: 97%
“…erraticus at the site generally peaked in the late summer and early autumn, when white-tailed deer were intensively targeted by this species. Deer can become infected with EEEV, and infected animals develop symptoms consistent with EEEV-induced neurological disease (Tate et al 2005, Schmitt et al 2007). However, the role that deer play in the transmission dynamics of EEEV is undetermined.…”
Section: Discussionmentioning
confidence: 99%